Off-Design Performance Analysis of Axial Flow Fan in Helicopter - 李明 高红霞 余建祖 迟蓬涛 (东华大学学报（英文版）, 2011)
A theoretical calculation method of off-design performance is developed for an axial flow fan of oil cooling system in helicopter,including calculation of aerodynamic parameters and performance parameters.When calculating inlet shock loss,the shock loss coefficient is obtained by comparing results of theoretical calculation,experimental and numerical calculation.The theoretical results and numerical results show that all air velocity components increase from hub to shroud in main flow area at rated condition.Tip leakage vortex moves downstream as flow rate increases.When flow rate decreases,Re decreases,and boundary layer thickness from hub to shroud area all increases gradually.Tip leakage vortex moves upstream,and secondary loss increases.Low speed area in the passage is widened along with high speed area moving to hub area,influenced by boundary layer separation.Consequently wake area and jet area at fan outlet are both larger than rated condition.Therefore optimization design for off-design performance of the fan is required on aerodynamic parameters influencing fan loss.A reliable method is supplied for estimating altitude performance of lubricating system in helicopter.